The environment and activity of Jakub Przyłuski as a district writer in Przemyśl - Grin-Piszczek, Ewa (Jakub Przyłuski (1512–1554): Outline of life and literary work against the background of the epoch, 2022)
In the years 1539–1547, Jakub Przyłuski was associated with Przemyśl, where he was a clerk of the petty offence court. He was appointed at this position due to the protection of Piotr Kmita, Przemyśl starosta. As a court writer, he dealt mainly with the supervision and organization of the work of a district office. He also prepared, inter alia, entries that started a given book. He had contacts with some representatives of the clergy elite and the laity in Przemyśl. In the years 1547–1548 he became the parish priest in Mościska.